Evolution of Interpersona Communication Through Symbols (Sticker) Cyber Native In The Line App - Noor Aini Rachmawati; Oryza Devi Salam; Giovani Anggasta Setiawan; Regina Geovania Anggasita Izaak (Bina Nusantara University, 2021)
The essence of man in life is to conduct communication activities. An individual is said to communicate with others if both have an understanding of the meaning of the message conveyed in his interaction. Advances in information communication technology provide opportunities for individuals to more easily interact over the internet. Of the recorded internet users, 130 million are active on social media. New Media Communication, or communication based on information technology, makes social media a prima donna for individuals to interact socially in cyberspace. Text-based communication platforms such as WhatsApp and LINE make it easier for individuals or those in cyberspace referred to as digital natives to interact. These digital natives in their interactions do the continuous thing as a habit that eventually becomes a culture of communication. In this research, the focus of research is the evolution of communication between users in the new media era in LINE users as a text application-based social media with a constructivist approach, qualitative research methodology with virtual ethnographic research methods and descriptive analysis levels. Data collection with online interviews, as well as chat history observations and the use of LINE sticker features. The purpose of the study is: (1) to find out the communication of digital natives on the LINE application platform, (2) to find out the evolution of interpersona communication formed from the results of native digital interactions on the LINE application platform using a virtual ethnographic approach.